Improving Transparency and Accountability in Public-Private Partnerships : Disclosure Diagnostic Report - Honduras - World Bank (World Bank, Washington, DC, 2018)
A joint Government of Honduras and World Bank team conducted a study in Honduras between January and June 2017, using the Public-Private Partnership (PPP) Disclosure Diagnostic template recommended by the World Bank Framework for Disclosure of Information in PPPs. This study has been consolidated in the form of a PPP Disclosure Diagnostic Report for Honduras. The Diagnostic Report examines the political, legal, and institutional environment for disclosure in PPPs. Based on a gap assessment exercise with key political, legal, institutional, and process findings benchmarked against the World Bank Framework, the Diagnostic Report makes specific recommendations to improve disclosure. The recommendations include a customized framework for disclosure of PPPs in Honduras.